A sintered NdFeB magnet and a method for preparing the same
By using metal Co and other elements as composite diffusion sources in the sintered NdFeB magnet for grain boundary diffusion treatment, the shortcomings of NdFeB magnet in temperature stability and corrosion resistance are solved, and the effect of significantly improving the magnet corrosion resistance, temperature stability and magnetic properties is achieved.
Patent Information
- Application Number
- CN202211098351.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-08
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-09-08
AI Technical Summary
The existing neodymium iron boron magnets have shortcomings in temperature stability and corrosion resistance, and it is difficult to maintain the high magnetic properties of the magnet by directly adding or using Co as a diffusion source.
By using metal Co and other elements such as Ga, Al, and Cu as composite diffusion sources in the sintered NdFeB magnet, the grain boundary diffusion process is carried out, so that the element Co is mainly concentrated in the grain boundary phase without entering the main phase of the grain in large quantities, thereby achieving the gradient distribution of element Co.
The corrosion resistance, temperature stability and magnetic properties of sintered NdFeB magnets are significantly improved, electrochemical corrosion is reduced, Curie temperature is improved, while maintaining high magnetic properties.
Smart Images

Figure CN115346746B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of NdFeB system sintered magnets, in particular to a sintered NdFeB magnet with high corrosion resistance, high Curie temperature and high magnetic properties and a preparation method thereof. Background Art
[0002] Since its discovery, NdFeB permanent magnet materials have been widely used in communications, medical, automotive, electronics, aviation and other fields due to their excellent magnetic properties and high cost performance. They have become ideal materials for manufacturing magnetic functional materials with high efficiency, small size and light weight, and have a revolutionary impact on many application fields. However, this type of material has poor temperature stability. At the same time, the main component of the material contains a high level of rare earth elements, so the corrosion resistance is poor. These two problems seriously limit the expansion of its application range.
[0003] In order to improve the corrosion resistance and temperature stability of NdFeB materials, the prior art usually introduces the element Co into NdFeB materials. Directly adding the element Co has limited effect on the corrosion resistance and temperature stability of NdFeB materials, and the element Co is mainly distributed inside the main phase grains, causing certain damage to the magnetic properties; using the element Co as a diffusion source to perform grain boundary diffusion treatment on the NdFeB material, since the melting point of the element Co is 1495°C, a higher diffusion temperature is required, which in turn causes the melting of the main phase grains, thereby changing the composition and organizational morphology of the main phase and reducing the performance of the magnet. This ultimately makes it impossible to maintain the high magnetic properties of the magnet while improving the corrosion resistance and temperature stability of NdFeB materials by directly adding the element Co and using the element Co as a diffusion source. Summary of the invention
[0004] After conducting an in-depth study on the above-mentioned problems, the inventors of the present application found that the element Co in the grain boundary phase plays a major role in improving the corrosion resistance and magnetic properties of the magnet. The advantage of grain boundary diffusion treatment is that the introduced elements are enriched in the grain boundary phase, and will not enter the main phase of the grain in large quantities. Due to the high melting point of metal Co, it is limited to be used as a single diffusion source. When metal Co and other components such as RL and / or RH are used as diffusion sources for composite diffusion treatment, the melting point of the diffusion source will decrease, but the enrichment of RH and / or RL elements in the grain boundary phase will hinder the Co element from continuing to enter the grain boundary phase, so that the Co element rarely or almost never enters the grain boundary phase; when metal Co and low-melting-point metal M1 (at least one of Ga, Al, and Cu) are used as diffusion sources for composite diffusion treatment, the melting point of the diffusion source is significantly reduced, and the element M1 (at least one of Ga, Al, and Cu) can play a role in thickening the grain boundary after entering the grain boundary, reserving a channel for the subsequent further diffusion of Co, and a small amount of added element M1 (at least one of Ga, Al, and Cu) can compensate for the reduction in coercivity caused by the addition of element Co.
[0005] In view of the above problems and findings, the present invention provides a sintered NdFeB magnet and a preparation method thereof, wherein the sintered NdFeB magnet includes the element Co, which is distributed in the grain boundary phase of the grains and the main phase of the grains, and the concentration of the element Co is distributed in a gradient from the surface to the center of the sintered NdFeB magnet, and the content of the element Co distributed in the grain boundary phase of the grains is greater than or equal to the content of the element Co distributed in the main phase of the grains. Since the element Co in the sintered NdFeB magnet is mainly concentrated in the grain boundary phase, this can significantly improve the corrosion resistance, temperature stability and magnetic properties of the sintered NdFeB magnet.
[0006] The technical solution of the present invention is as follows:
[0007] A sintered NdFeB magnet, comprising an element Co whose content is greater than 0 and less than or equal to 3.0wt%, and comprising a main phase and a grain boundary phase; the element Co is distributed in the grain boundary phase of the grains and the main phase of the grains; the sintered NdFeB magnet satisfies: w1≥w2, w3≥w4, wherein w1 is the content of the element Co on the surface of the magnet, w2 is the content of the element Co at the center of the magnet, w3 is the content of the element Co distributed in the grain boundary phase of the grain at a distance H from the magnet surface, w4 is the content of the element Co distributed in the main phase of the grain at a distance H from the magnet surface, and H is 0-400μm.
[0008] In the present invention, unless otherwise specified, the content mentioned refers to the mass percentage.
[0009] According to an embodiment of the present invention, the sintered NdFeB magnet satisfies: w3≥1.5×w4, w3 is the content of the element Co distributed in the grain boundary phase of the grain at a distance H from the magnet surface, and w4 is the content of the element Co distributed in the main phase of the grain at a distance H from the magnet surface.
[0010] According to an embodiment of the present invention, the sintered NdFeB magnet satisfies: w5≥w6, w5 is the content of the element Co distributed in the grain boundary phase of the grain at a distance h1 from the magnet surface, w6 is the content of the element Co distributed in the grain boundary phase of the grain at a distance h2 from the magnet surface, and 0≤h1 <h2≤400μm。
[0011] According to an embodiment of the present invention, the sintered NdFeB magnet satisfies: w7≥w8, w7 is the content of the element Co distributed in the main phase of the grain at a distance h1 from the magnet surface, w8 is the content of the element Co distributed in the main phase of the grain at a distance h2 from the magnet surface, and 0≤h1 <h2≤400μm。
[0012] According to an embodiment of the present invention, the sintered NdFeB magnet satisfies: w9>w10, w9 is the content of element Co at a distance h1 from the magnet surface, w10 is the content of element Co at a distance h2 from the magnet surface, and 0≤h1 <h2≤400μm。
[0013] According to an embodiment of the present invention, in the sintered NdFeB magnet, the Co-enriched region and the heavy rare earth-enriched region in the grain boundary phase do not completely overlap.
[0014] According to an embodiment of the present invention, in the sintered NdFeB magnet, the Co-enriched region in the grain boundary phase is an Fe-poor region.
[0015] According to an embodiment of the present invention, in the sintered NdFeB magnet, the grain boundary phase contains a phase composed of RFeCoM1M2, where R is a rare earth element, Fe is iron, Co is cobalt, M1 is at least one of Ga, Al, and Cu, and M2 is at least one of Zr and Ti.
[0016] According to an embodiment of the present invention, in the sintered NdFeB magnet, the content of the R element in the grain boundary phase is ≥ the content of the R element in the main phase.
[0017] According to an embodiment of the present invention, in the sintered NdFeB magnet, the content of the M1 element in the grain boundary phase is ≥ the content of the M1 element in the main phase.
[0018] According to an embodiment of the present invention, in the sintered NdFeB magnet, the content of the M2 element in the grain boundary phase is ≥ the content of the M2 element in the main phase.
[0019] According to an embodiment of the present invention, in the sintered NdFeB magnet, the content of Fe in the grain boundary phase is ≤ the content of Fe in the main phase.
[0020] According to an embodiment of the present invention, the sintered NdFeB magnet includes an element Co content greater than 0 and less than or equal to 3.0wt%, for example, it includes an element Co content of 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt% or 3.0wt%.
[0021] According to an embodiment of the present invention, the chemical formula of the sintered NdFeB magnet is RFeCoBM1M2, wherein R is a rare earth element, Fe is iron, B is boron, M1 is at least one of Ga, Al, and Cu, and M2 is at least one of Zr and Ti, wherein the R content is 26wt% to 35wt%, the B content is 0.8wt% to 1.3wt%, the Co content is 0 to 3.0wt%, the Ga content is 0.05wt% to 0.5wt%, the Cu content is 0.05wt% to 0.6wt%, the Al content is 0wt% to 1.5wt%, the Zr content is 0wt% to 1wt%, the Ti content is 0wt% to 1wt%, and the remainder is iron and unavoidable impurities, and the Co content is not 0, and the sum of the Zr and Ti contents is not 0.
[0022] According to an embodiment of the present invention, R is a rare earth element, for example, at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), yttrium (Y) and scandium (Sc).
[0023] The present invention also provides a method for preparing the sintered NdFeB magnet, comprising the following steps:
[0024] 1) Preparation of R-Fe-Co-B-M1-M2 sintered magnet;
[0025] 2) processing the sintered magnet of step 1) into a required size and then performing pretreatment;
[0026] 3) mixing metal powder containing M1 and Co, an antioxidant and an organic solvent, stirring evenly to obtain a diffusion slurry, wherein M1 is at least one of Cu, Ga and Al;
[0027] 4) placing the diffusion slurry obtained in step 3) on the surface of the sintered magnet obtained in step 2), and then drying it;
[0028] 5) Under vacuum conditions, subjecting the magnet obtained in step 4) to grain boundary diffusion treatment, and cooling to room temperature after the heat preservation process is completed;
[0029] 6) subjecting the magnet obtained in step 5) to aging treatment to prepare the sintered NdFeB magnet.
[0030] According to an embodiment of the present invention, in step 1), in the R-Fe-Co-B-M1-M2 sintered magnet, R is a rare earth element, Fe is iron, Co is cobalt, B is boron, M1 is at least one of Ga, Al, and Cu, and M2 is at least one of Zr and Ti, wherein the R content is 26wt% to 35wt%, the B content is 0.8wt% to 1.3wt%, the Co content is 0 to 1.5wt% (preferably 0 to 0.5wt%), the Ga content is 0.05wt% to 0.5wt%, the Cu content is 0.05wt% to 0.6wt%, the Al content is 0wt% to 1.5wt%, the Zr content is 0wt% to 1wt%, the Ti content is 0wt% to 1wt%, and the remainder is iron and unavoidable impurities, and the sum of the Zr and Ti contents is not 0.
[0031] According to an embodiment of the present invention, in step 1), R is at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), yttrium (Y) and scandium (Sc).
[0032] According to an embodiment of the present invention, in step 1), the R-Fe-Co-B-M1-M2 sintered magnet is prepared by a method well known to those skilled in the art, including a smelting process, a powder making process, a green compacting process, a sintering treatment process and an aging treatment process.
[0033] According to an embodiment of the present invention, in step 2), the pretreatment includes cleaning, degreasing, pickling and drying the processed sintered magnet.
[0034] According to an embodiment of the present invention, in step 3), the metal powder containing M1 and Co is a mixed powder prepared from M1 and Co, such as an alloy powder prepared; illustratively, the metal powder containing M1 and Co is at least one of Cu-Co powder, Ga-Co powder, Al-Co powder, Cu-Ga-Co powder, Cu-Al-Co powder, Ga-Al-Co powder, and Cu-Ga-Al-Co powder. For example, the Cu-Co powder specifically refers to a metal powder containing element Cu and element Co, such as an alloy powder containing Cu and Co.
[0035] According to an embodiment of the present invention, in step 3), the method for preparing the metal powder containing M1 and Co is to smelt and powder the raw materials of metal M1 (at least one of Cu, Ga, Al) and metal Co to obtain alloy powder.
[0036] According to an embodiment of the present invention, in step 3), the content of element Co in the metal powder containing M1 and Co is 10 to 50 wt%, for example, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt% or 50 wt%; when the content of Co is too low, the distribution uniformity of Co in the diffusion slurry deteriorates, resulting in uneven distribution of Co arranged on the surface of the pretreated magnet; when the content of Co is too high, the viscosity of the diffusion slurry increases, the fluidity deteriorates, and the melting point also increases, making it difficult to arrange a diffusion slurry of uniform thickness on the surface of the pretreated magnet, and the temperature of the diffusion treatment needs to be increased subsequently.
[0037] According to an embodiment of the present invention, in step 3), the average particle size of the metal powder containing M1 and Co is controlled within 50 μm. When the average particle size of the powder exceeds 50 μm, it is difficult to form a uniform diffusion slurry.
[0038] According to an embodiment of the present invention, in step 3), the antioxidant is selected from at least one of 1,3,5-trichlorotoluene, 4-hexylresorcinol and butylated hydroxytoluene; the organic solvent is selected from at least one of alcohols, ketones, ethers, such as ethanol, benzyl alcohol and acetone.
[0039] According to an embodiment of the present invention, in step 4), the arrangement method may be at least one of thermal spraying, coating, sputtering, dipping, and the like.
[0040] According to an embodiment of the present invention, in step 4), the thickness of the diffusion slurry is 10 μm to 200 μm. If the thickness is too small, it is difficult to achieve uniform distribution of powder particles. If the thickness is too large, excess diffusion slurry is prone to agglomerate on the surface, affecting the surface state and performance of the magnet.
[0041] According to an embodiment of the present invention, in step 4), the drying temperature is 50°C to 200°C (for example, 50°C, 70°C, 80°C, 90°C, 100°C, 120°C, 140°C, 150°C, 160°C, 180°C or 200°C), and the drying is carried out under an inert atmosphere (nitrogen, argon, etc.).
[0042] According to an embodiment of the present invention, in step 5), the temperature of the diffusion treatment is 850°C to 950°C (850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C or 950°C), preferably, the temperature of the diffusion treatment is 880°C to 930°C.
[0043] According to an embodiment of the present invention, in step 5), the insulation time is more than 3 hours, for example, 3 hours to 24 hours, such as 3 hours, 6 hours, 8 hours, 9 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours or 24 hours.
[0044] According to an embodiment of the present invention, in step 6), the temperature of the aging treatment is 400-600° C., and the time of the aging treatment is 2-10 hours.
[0045] According to an embodiment of the present invention, in step 6), the prepared sintered NdFeB magnet may be further subjected to RH and / or RL grain boundary diffusion treatment.
[0046] Beneficial effects of the present invention:
[0047] The invention provides a sintered NdFeB magnet and a preparation method thereof. The sintered NdFeB magnet comprises element Co, and the sintered NdFeB magnet comprises a main phase and a grain boundary phase; the element Co is distributed in the grain boundary phase of the grain and the main phase of the grain, and the sintered NdFeB magnet satisfies: w1≥w2, w3≥w4, wherein w1 is the content of the element Co on the surface of the magnet, w2 is the content of the element Co at the center of the magnet, w3 is the content of the element Co distributed in the grain boundary phase of the grain at a distance H from the magnet surface, and w4 is the content of the element Co distributed in the main phase of the grain at a distance H from the magnet surface, and H is 0-400 μm.
[0048] Sintered NdFeB magnets mainly include main phase and grain boundary phase. Because there is a potential difference between the main phase and the grain boundary phase, electrochemical corrosion will occur. Since the grain boundary phase is a Nd-rich phase, its electrode potential is lower, and electrochemical corrosion will occur preferentially. The inventors of the present application unexpectedly found that by concentrating the element Co in the grain boundary phase, the element Co can form a Nd3Co phase with the Nd-rich phase. The formation of the Nd3Co phase improves the electrode potential of the entire grain boundary phase, reduces the degree of electrochemical corrosion, and greatly reduces the weight loss of the magnet. The corrosion resistance of the NdFeB magnet is significantly improved, and the magnetic properties of the sintered NdFeB magnet can also be significantly improved. At the same time, Co is enriched at the grain boundary, and the main phase grains are wrapped inside, which can protect the main phase grains and effectively improve the Curie temperature of the magnet.
[0049] The present application arranges a diffusion slurry prepared by metal powder containing M1 and Co (the content of element Co in the metal powder is 10 to 50 wt%), an antioxidant and an organic solvent on the surface of a sintered magnet, performs a drying treatment, and then performs a grain boundary diffusion treatment on the dried magnet at 850 to 950°C under vacuum conditions for more than 3 hours. A sintered NdFeB magnet can be obtained in which the concentration of element Co is gradiently distributed from the surface of the magnet to the center, the content of element Co distributed in the grain boundary phase of the grain at 0 to 400 μm from the surface of the magnet is greater than or equal to the content of element Co distributed in the main phase of the grain, and the corrosion resistance and Curie temperature of the NdFeB magnet are improved while maintaining the high magnetic properties of the magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 : Element distribution diagram of the sintered NdFeB magnet A0-1 in Example 1 scanned using EPMA;
[0051] Figure 2 : Element distribution diagram of the sintered NdFeB magnet A1 in Example 1 scanned using EPMA;
[0052] Figure 3 : EPMA scan of the Co element content variation of the sintered NdFeB magnet A0-1 in Example 1;
[0053] Figure 4 : EPMA was used to scan the Co element content variation of the sintered NdFeB magnet A1 in Example 1. DETAILED DESCRIPTION
[0054] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0055] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0056] Example 1
[0057] (1) The raw materials NdPr, Dy, Co, Al, Fe, Cu, Ga, Zr, Ti and BFe are cast in a vacuum melting furnace in an argon atmosphere to form a flake alloy. The flake alloy composition is 31.5% NdPr, 0.5% Dy, 1.0% Co, 0.15% Al, 0.18% Cu, 0.25% Ga, 0.18% Ti, 0.99% B by mass, and the balance is iron and inevitable impurities; the flake alloy is hydrogen crushed and air flow milled to obtain an alloy powder with an average particle size of 3.5 μm; the flake alloy is pressed and formed at room temperature and a magnetic field intensity of 2T orientation field; the formed body is placed in a vacuum sintering furnace and sintered at 1050°C for 5 hours to obtain a green body, and the green body is aged at 500°C for 5 hours to obtain an R-Fe-Co-B-M1-M2 sintered magnet.
[0058] (2) The magnet is processed into square pieces with a size of 25-20-5 mm, where 5 mm is the thickness of the square piece in the orientation direction. The magnet obtained after the square piece is cleaned, degreased, pickled and dried is marked as A0-1.
[0059] (3) Metal Cu and metal Co are poured into a vacuum melting furnace at a mass percentage of 70% Cu and 30% Co to form an alloy. The alloy is crushed by hydrogen and jet milled to obtain a powder with an average particle size of 3.0 μm. The obtained powder is then mixed with butylated hydroxytoluene and ethanol in a mass ratio of 7:2:1 and stirred for 2 hours to obtain a diffusion slurry containing Co.
[0060] (4) The obtained diffusion slurry was arranged on the surface of magnet A0-1 by thermal spraying method. The slurry thickness was 100 μm and dried at 70° C. in an argon atmosphere.
[0061] (5) The dried square pieces were subjected to grain boundary diffusion treatment in a vacuum state at a diffusion temperature of 920° C. for 10 h, and then cooled to room temperature.
[0062] (6) The diffused square sheet was aged at 500°C for 5 h, and the obtained product was recorded as A1.
[0063] Example 2
[0064] The preparation method of this embodiment is basically the same as that of embodiment 1, except that in step 2), the magnet obtained after the square pieces are cleaned, degreased, pickled and dried is denoted as A0-2; in step (3), metal Ga and metal Co are put into a vacuum melting furnace at a mass percentage of 70% Ga and 30% Co to complete casting to form a flake alloy; and the final product is denoted as A2.
[0065] Example 3
[0066] The preparation method of this embodiment is basically the same as that of embodiment 1, except that in step 2), the magnet obtained after the square pieces are cleaned, degreased, pickled and dried is denoted as A0-3; in step (3), metal Al and metal Co are put into a vacuum melting furnace at a mass percentage of 70% Al and 30% Co to complete casting to form a flake alloy; and the final product is denoted as A3.
[0067] Example 4
[0068] The preparation method of this embodiment is basically the same as that of embodiment 1, except that in step 2), the magnet obtained after the square pieces are cleaned, degreased, pickled and dried is denoted as A0-4; in step (3), metal Cu, metal Ga and metal Co are put into a vacuum melting furnace at a mass percentage of 30% Cu, 40% Ga and 30% Co to complete casting to form a flake alloy; the final product is denoted as A4.
[0069] Example 5
[0070] The preparation method of this embodiment is basically the same as that of embodiment 1, except that in step 2), the magnet obtained after the square pieces are cleaned, degreased, pickled and dried is denoted as A0-5; in step (3), metal Cu, metal Al and metal Co are put into a vacuum melting furnace in a mass percentage of 30% Cu, 40% Al and 30% Co to complete casting to form a flake alloy; the final product is denoted as A5.
[0071] Example 6
[0072] The preparation method of this embodiment is basically the same as that of embodiment 1, except that in step 2), the magnet obtained after the square pieces are cleaned, degreased, pickled and dried is denoted as A0-6; in step (3), metal Ga, metal Al and metal Co are put into a vacuum melting furnace at a mass percentage of 30% Ga, 40% Al and 30% Co to complete casting to form a flake alloy; the final product is denoted as A6.
[0073] Example 7
[0074] The preparation method of this embodiment is basically the same as that of embodiment 1, except that in step 2), the magnet obtained after the square flakes are cleaned, degreased, pickled and dried is denoted as A0-7; in step (3), metal Cu, metal Ga, metal Al and metal Co are put into a vacuum melting furnace in a mass percentage of 30% Cu, 20% Ga, 20% Al and 30% Co to complete casting to form a flake alloy; the final product is denoted as A7.
[0075] Example 8
[0076] The preparation method of this embodiment is basically the same as that of Embodiment 7, except that the alloy composition of the flakes in step (1) is 31.5% NdPr, 0.5% Dy, 0.15% Al, 0.18% Cu, 0.25% Ga, 0.18% Ti, 0.99% B, and the remainder is iron and unavoidable impurities; the magnet obtained after the square flakes are cleaned, degreased, pickled and dried in step 2) is denoted as A0-8; and the final product obtained in step (3) is denoted as A8.
[0077] Example 9
[0078] The preparation method of this embodiment is basically the same as that of Embodiment 7, except that the alloy composition of the flakes in step (1) is 31.5% NdPr, 0.5% Dy, 0.5% Co, 0.15% Al, 0.18% Cu, 0.25% Ga, 0.18% Ti, 0.99% B, and the remainder is iron and unavoidable impurities; the magnet obtained after the square flakes are cleaned, degreased, pickled and dried in step 2) is denoted as A0-9; and the final product obtained in step (3) is denoted as A9.
[0079] Example 10
[0080] The preparation method of this embodiment is basically the same as that of Example 7, except that the alloy composition of the flakes in step (1) is 31.5% NdPr, 0.5% Dy, 1.5% Co, 0.15% Al, 0.18% Cu, 0.25% Ga, 0.18% Ti, 0.99% B, and the remainder is iron and unavoidable impurities; the magnet obtained after the square flakes are cleaned, degreased, pickled and dried in step 2) is denoted as A0-10; and the final product obtained in step (3) is denoted as A10.
[0081] Embodiment 11
[0082] The preparation methods of this embodiment are basically the same as those of embodiment 7, except that in step 2), the magnet obtained after the square pieces are cleaned, degreased, pickled and dried is denoted as A0-11; in step (3), metal Cu, metal Ga, metal Al and metal Co are put into a vacuum melting furnace in a mass percentage of 30% Cu, 30% Ga, 30% Al and 10% Co to complete casting to form a flake alloy; the final product is denoted as A11.
[0083] Example 12
[0084] The preparation methods of this embodiment are basically the same as those of embodiment 7, except that in step 2), the magnet obtained after the square pieces are cleaned, degreased, pickled and dried is denoted as A0-12; in step (3), metal Cu, metal Ga, metal Al and metal Co are put into a vacuum melting furnace at a mass percentage of 20% Cu, 15% Ga, 15% Al and 50% Co to complete casting to form a flake alloy; the final product is denoted as A12.
[0085] Comparative Example 1
[0086] The preparation method of this comparative example is basically the same as that of Example 7, except that the alloy composition of the flakes in step (1) is 31.5% NdPr, 0.5% Dy, 2.0% Co, 0.15% Al, 0.18% Cu, 0.25% Ga, 0.18% Ti, 0.99% B, and the remainder is iron and unavoidable impurities; the magnet obtained after the square flakes are cleaned, degreased, pickled and dried in step 2) is recorded as B0-1; the final product obtained in step (3) is recorded as B1.
[0087] Comparative Example 2
[0088] The preparation method of this comparative example is basically the same as that of Example 7, except that in step 2), the magnet obtained after the square flakes are cleaned, degreased, pickled and dried is recorded as B0-2; in step (3), metal Cu, metal Ga, metal Al and metal Co are put into a vacuum melting furnace at a mass percentage of 35% Cu, 30% Ga, 30% Al and 5% Co to complete casting to form a flake alloy; the final product is recorded as B2.
[0089] Comparative Example 3
[0090] The preparation method of this comparative example is basically the same as that of Example 7, except that in step 2), the magnet obtained after the square pieces are cleaned, degreased, pickled and dried is recorded as B0-3; in step (3), metal Cu, metal Ga, metal Al and metal Co are put into a vacuum melting furnace in a mass percentage of 15% Cu, 15% Ga, 10% Al and 60% Co to complete casting to form a flake alloy; the final product is recorded as B3.
[0091] Comparative Example 4
[0092] The preparation method of this comparative example is basically the same as that of Example 1, except that in step 2), the magnet obtained after the square sheet is cleaned, degreased, pickled and dried is recorded as B0-4; in step (3), the metal Co is hydrogen crushed and jet milled to obtain a powder with an average particle size of 3.0 μm, and then the obtained powder is mixed with butylated hydroxytoluene and ethanol in a mass ratio of 7:2:1, and stirred for 2 hours to obtain a diffusion slurry containing Co; at the same time, due to the high melting point of Co, the diffusion temperature is set to 950°C; the final product is recorded as B4.
[0093] Table 1 Magnetic properties and corrosion resistance of A0-1, A1~A12, B1~B4
[0094]
[0095]
[0096] The final products A1-A7 of Examples 1-7 are compared with the product A0-1 in Example 1 without diffusion treatment: the weight loss of A1-A7 is equivalent and significantly better than A0-1; the magnetic properties of A1-A7 are equivalent to A0-1. This is mainly because the magnets prepared by the methods of Examples 1-7 can ensure sufficient distribution of the element Co in the grain boundary phase, improve the corrosion resistance of the product, and at the same time, the addition of Ga, Cu, and Al elements can compensate for the reduction in coercivity caused by the addition of Co.
[0097] Compared with the final product B1 of Comparative Example 1, the weight loss of the final products A7-A10 of Examples 7-10 is similar to that of B1, but the magnetic properties of B1 are reduced. This is mainly because the Co content (2.0wt%) of the matrix of Comparative Example 1 is relatively high. After the grain boundary diffusion treatment with the Co-containing diffusion slurry, too much Co element is introduced into the product, which in turn leads to a decrease in the magnetic properties.
[0098] Compared with the final products A7, A11, A12 of Examples 7, 11, and 12 and the final products B2 and B3 of Comparative Examples 2 and 3: the weight loss of A7, A11, A12, and B3 is equivalent, and the magnetic properties of A7, A11, A12, and B2 are equivalent, but the weight loss of B2 is large (i.e., the corrosion resistance is poor) and the magnetic properties of B3 are reduced. This is mainly because the content of Co element in the diffusion slurry of Comparative Example 2 is relatively low (<10wt%), resulting in less Co element introduced into the final product and less improvement in corrosion resistance. The content of Co element in the diffusion slurry of Comparative Example 3 is relatively high (>50wt%), and the product introduces too much Co element, which in turn leads to a decrease in magnetic properties.
[0099] Furthermore, the Curie temperatures of the final product A-1 of Example 1 and the product A0-1 of Example 1 without diffusion treatment were tested by the MT curve test method, that is, the curves of the change of their magnetization intensity with temperature were tested respectively, and the temperature corresponding to the maximum value of dM / dT was Tc.
[0100] Table 2 Curie temperature of A0-1 and A-1
[0101] Matrix Co (wt%) Diffusion source Curie temperature Tc(℃) A0-1 1 —— 321.3 A-1 1 <![CDATA[Cu 70 Co 30 ]]> 353.2
[0102] It can be seen from Table 2 that the Curie temperature of the final product A-1 of Example 1 is significantly higher than that of the product A0-1 without diffusion treatment in Example 1. This is mainly because after the grain boundary diffusion treatment with the Co-containing diffusion source, the element Co enters the grain boundary and plays a role in protecting the main phase grains, thereby increasing the Curie temperature of the product and improving the temperature stability of the product.
[0103] Furthermore, for product A1 of Example 1 and product B4 of the comparative example, the Co content of the large surface of 25-20 mm was tested by XRF; 50 μm was ground off along the magnetizing direction and polished, and the Co content of the large surface of 25-20 mm was tested by XRF; in this way, the Co content of the large surfaces of 100 μm, 200 μm, 300 μm, 400 μm, 410 μm, 420 μm, 1 mm, 2 mm and 2.5 mm (center) ground off along the magnetizing direction was tested in turn.
[0104] Table 3 Concentration distribution of element Co content in A1 and B4
[0105] Different locations Elemental Co content of A1 Elemental Co content of B4 Magnet surface 2.31% 2.52% 50μm from the magnet surface 1.65% 1.22% 100μm from the magnet surface 1.39% 1.07% 200μm from the magnet surface 1.20% 1.03% 300μm from the magnet surface 1.12% 1.00% 400μm from the magnet surface 1.05% 1.00% 410μm from the magnet surface 1.05% 1.00% 420μm from the magnet surface 1.05% 1.00% 1mm from the magnet surface 1.03% 1.00% 2mm from the magnet surface 1.00% 1.00% 2.5mm from the magnet surface 1.00% 1.00%
[0106] It can be seen from Table 3 that the concentration of element Co in product A1 of Example 1 is distributed in a gradient from the surface to the center of the sintered NdFeB magnet. This is mainly because after the product is treated with grain boundary diffusion containing a Co diffusion source, element Co enters the interior of the magnet. As the depth increases, the amount of Co element diffused into the interior of the magnet decreases. The maximum diffusion depth that element Co can reach is about 400 μm from the magnet surface. The concentration of element Co in product B4 of comparative example 4 is mainly distributed in the area 0 to 50 μm from the magnet surface. This is mainly because the melting point of metal Co is high. Even if the diffusion temperature is increased when pure metal Co powder is used for grain boundary diffusion treatment, it is still difficult for element Co to enter deep into the magnet.
[0107] Furthermore, the products A0-1, A1-A3 of Examples 1-3 were processed into products of 10-10-5 mm, and 0.05 mm was ground off along the magnetization direction (5 mm direction) and then the 10-10 mm large surface was scanned using EPMA. The structure and composition of the main phase and grain boundary phase were observed by scanning, among which, Figure 1 The element distribution diagram of the sintered NdFeB magnet A0-1 in Example 1 was scanned using EPMA. Figure 2 EPMA is used to scan the element distribution of the sintered NdFeB magnet A1 in Example 1. Figure 3 The Co element content variation diagram of the sintered NdFeB magnet A0-1 in Example 1 was scanned using EPMA. Figure 4 The Co element content variation diagram of the sintered NdFeB magnet A1 in Example 1 was scanned using EPMA.
[0108] from Figure 1 and Figure 3 It can be seen from the graph that the element Co is distributed in the grain boundary phase and the main phase of the grain, and the content of the element Co distributed in the grain boundary phase is less than the content of the element Co distributed in the main phase of the grain. Figure 2 and Figure 4 It can be seen that the element Co is also distributed in the grain boundary phase of the grains and the main phase of the grains, but the content of the element Co distributed in the grain boundary phase of the grains is greater than the content of the element Co distributed in the main phase of the grains.
[0109] Table 4 Co content of sintered NdFeB magnets A0-1 and A1
[0110]
[0111] It can be seen from Table 4 that after grain boundary diffusion treatment with a Co-containing diffusion source, the Co content in the grain boundary phase of the sintered NdFeB magnet is more than 1.5 times the Co content in the main phase of the grain. Preferably, the Co content in the grain boundary phase of the sintered NdFeB magnet is more than 2 times the Co content in the main phase of the grain.
[0112] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A sintered NdFeB magnet, characterized in that: The sintered NdFeB magnet includes the element Co whose content is greater than 0 and less than or equal to 3.0wt%, and the sintered NdFeB magnet includes a main phase and a grain boundary phase; the element Co is distributed in the grain boundary phase of the grain and the main phase of the grain; the sintered NdFeB magnet satisfies: w1≥w2, w3≥w4, wherein w1 is the content of the element Co on the surface of the magnet, w2 is the content of the element Co at the center of the magnet, w3 is the content of the element Co distributed in the grain boundary phase of the grain at a distance H from the surface of the magnet, and w4 is the content of the element Co distributed in the main phase of the grain at a distance H from the surface of the magnet, and H is 0~400μm; The sintered NdFeB magnet satisfies: w5≥w6, w5 is the content of the element Co distributed in the grain boundary phase of the grain at a distance h1 from the magnet surface, w6 is the content of the element Co distributed in the grain boundary phase of the grain at a distance h2 from the magnet surface, and 0≤h1 <h2≤400μm; The sintered NdFeB magnet satisfies: w7≥w8, w7 is the content of the element Co distributed in the main phase of the grain at a distance h1 from the magnet surface, w8 is the content of the element Co distributed in the main phase of the grain at a distance h2 from the magnet surface, and 0≤h1 <h2≤400μm; The chemical formula of the sintered NdFeB magnet is RFeCoBM1M2, wherein R is a rare earth element, Fe is iron, B is boron, M1 is at least one of Ga, Al, and Cu, and M2 is at least one of Zr and Ti, wherein the R content is 26wt% to 35wt%, the B content is 0.8wt% to 1.3wt%, the Co content is 0 to 3.0wt%, the Ga content is 0.05wt% to 0.5wt%, the Cu content is 0.05wt% to 0.6wt%, the Al content is 0wt% to 1.5wt%, the Zr content is 0wt% to 1wt%, the Ti content is 0wt% to 1wt%, and the remainder is iron and unavoidable impurities, and the Co content is not 0, and the sum of the Zr and Ti contents is not 0; The sintered NdFeB magnet is prepared by arranging a diffusion slurry obtained by mixing metal powder containing M1 and Co, an antioxidant and an organic solvent on the surface of a R-Fe-Co-B-M1-M2 sintered magnet, wherein M1 is at least one of Cu, Ga and Al.
2. The sintered NdFeB magnet according to claim 1, characterized in that: The sintered NdFeB magnet satisfies: w3≥1.5×w4, w3 is the content of the element Co distributed in the grain boundary phase of the grain at a distance H from the magnet surface, and w4 is the content of the element Co distributed in the main phase of the grain at a distance H from the magnet surface.
3. The sintered NdFeB magnet according to claim 1, characterized in that: The sintered NdFeB magnet satisfies: w9>w10, w9 is the content of element Co at a distance h1 from the magnet surface, w10 is the content of element Co at a distance h2 from the magnet surface, and 0≤h1 <h2≤400μm。 4. The sintered NdFeB magnet according to claim 1, characterized in that: In the sintered NdFeB magnet, the Co-enriched region in the grain boundary phase does not completely overlap with the heavy rare earth-enriched region; And / or, in the sintered NdFeB magnet, the Co-enriched region in the grain boundary phase is an Fe-poor region.
5. The sintered NdFeB magnet according to claim 1, characterized in that: In the sintered NdFeB magnet, the grain boundary phase contains a phase composed of RFeCoM1M2, R is a rare earth element, Fe is iron, Co is cobalt, M1 is at least one of Ga, Al, and Cu, and M2 is at least one of Zr and Ti; and / or, the content of R element in the grain boundary phase ≥ the content of R element in the main phase; And / or, in the sintered NdFeB magnet, the content of M1 element in the grain boundary phase is ≥ the content of M1 element in the main phase; And / or, in the sintered NdFeB magnet, the content of M2 element in the grain boundary phase is ≥ the content of M2 element in the main phase; And / or, in the sintered NdFeB magnet, the content of Fe element in the grain boundary phase is ≤ the content of Fe element in the main phase.
6. A method for preparing a sintered NdFeB magnet according to any one of claims 1 to 5, characterized in that: The steps include: 1) Preparation of R-Fe-Co-B-M1-M2 sintered magnets; 2) Processing the sintered magnet in step 1) into required size and then pre-treating it; 3) Mixing metal powder containing M1 and Co, an antioxidant and an organic solvent, stirring evenly to obtain a diffusion slurry, wherein M1 is at least one of Cu, Ga and Al; 4) placing the diffusion slurry obtained in step 3) on the surface of the sintered magnet obtained in step 2) and then drying it; 5) Under vacuum conditions, subjecting the magnet obtained in step 4) to grain boundary diffusion treatment, and cooling to room temperature after the heat preservation process is completed; 6) The magnet obtained in step 5) is subjected to aging treatment to prepare the sintered NdFeB magnet.
7. The preparation method according to claim 6, characterized in that: In step 1), in the R-Fe-Co-B-M1-M2 sintered magnet, R is a rare earth element, Fe is iron, Co is cobalt, B is boron, M1 is at least one of Ga, Al, and Cu, and M2 is at least one of Zr and Ti, wherein the R content is 26wt%~35wt%, the B content is 0.8wt%~1.3wt%, the Co content is 0~1.5wt%, the Ga content is 0.05wt%~0.5wt%, the Cu content is 0.05wt%~0.6wt%, the Al content is 0wt%~1.5wt%, the Zr content is 0wt%~1wt%, the Ti content is 0wt%~1wt%, and the remainder is iron and unavoidable impurities, and the sum of the Zr and Ti contents is not 0.
8. The preparation method according to claim 7, characterized in that: The Co content is 0~0.5wt%.
9. The preparation method according to claim 6, characterized in that: In step 3), the metal powder containing M1 and Co is at least one of Cu-Co powder, Ga-Co powder, Al-Co powder, Cu-Ga-Co powder, Cu-Al-Co powder, Ga-Al-Co powder, and Cu-Ga-Al-Co powder; And / or, in step 3), the content of element Co in the metal powder containing M1 and Co is 10-50wt%; And / or, in step 3), the average particle size of the metal powder containing M1 and Co is controlled within 50 μm.
10. The preparation method according to claim 6, characterized in that: In step 4), the thickness of the diffusion slurry is 10 μm to 200 μm; And / or, in step 5), the temperature of the diffusion treatment is 850° C. to 950° C.; and the insulation time is more than 3 hours.
Citation Information
Patent Citations
Rare-earth magnet, method of manufacturing rare-earth magnet and rotator
CN102237168A
Method for improving coercive force of neodymium iron boron
CN113744985A